Spatial Modeling of Flood Risk Areas in Palembang City, South Sumatera (Journal of Wetlands Environmental Management, 2024)
Flooding in the city of Palembang is a serious problem for the government because it causes large property losses and continues to spread. Spatial analysis to identify flood-risk areas is very necessary to provide information as a first step in future flood disaster mitigation efforts. This research aims to identify factors that influence flood levels in Palembang City and create a spatial model of flood-risk areas in Palembang City. This research uses two approaches, namely Analytical Hierarchy Process (AHP) and Geographic Information System (GIS). The results show that, the parameter that has the highest influence is land use at 37 %, then the rainfall parameter at 21 %, the slope parameter at 17 %, drainage density parameter at 12 %, elevation parameter at 7 % and soil type parameter at 6 %. Based on the GIS method, it is known that the flood-risk very low level covering an area of 1,141,69 hectares (3.17 %), the low flood-risk level covering an area of 4.889,44 hectares (13.58 %). The moderate flood-risk level area (the most extensive level) is 12.125,47 hectares (33.67 %), the high flood-risk level is 9.183,52 hectares (25.50 %) and the very high flood-risk level area is 8.656,54 hectares (24.09 %).